2017
DOI: 10.1111/jvs.12505
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of compositional and structural diversity on forest productivity

Abstract: Questions Tree species diversity is widely reported to positively influence forest productivity. Yet, a consistent attribution of productivity effects is complicated by the fact that compositional and structural diversity are often related in forest ecosystems. Here, our objective was to disentangle the effects of diversity in species and structures on forest productivity. We further assessed whether the influence of structure and composition on productivity changes over the course of forest development. Locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 52 publications
(121 reference statements)
1
22
1
Order By: Relevance
“…However, numerous unresolved questions center on understanding which vegetation structural features are most closely tied to production and whether they change over time and across ecosystems. The principal vegetation structural determinant of forest production may change as ecosystem development unfolds over decades to centuries (Silva Pedro et al, 2017) and may differ among plant functional types (Scheuermann et al, 2018). Additionally, the successional context of ecosystems—in our study case, a forest in transition from early to middle stages—differentially influences the production response to disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous unresolved questions center on understanding which vegetation structural features are most closely tied to production and whether they change over time and across ecosystems. The principal vegetation structural determinant of forest production may change as ecosystem development unfolds over decades to centuries (Silva Pedro et al, 2017) and may differ among plant functional types (Scheuermann et al, 2018). Additionally, the successional context of ecosystems—in our study case, a forest in transition from early to middle stages—differentially influences the production response to disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of disturbance severity on indexes describing forest tree species diversity and vegetation structure and, separately, on NPP have been long theorized and observed (Clements, 1916; Pickett & White, 1985). However, these effects have rarely been examined together despite evidence of forest structure–function coupling in a number of ecological contexts (Scheuermann, Nave, Fahey, Nadelhoffer, & Gough, 2018; Silva Pedro, Rammer, & Seidl, 2017). Joint investigation of forest structure–function relationships is timely as the range of disturbance severities present on temperate forest landscapes expands and, consequently, broadly reshapes plant species diversity and vegetation structure (Seidl et al, 2017; Turner, 2010) and NPP (Stuart‐Haëntjens, Curtis, Fahey, Vogel, & Gough, 2015), sometimes in surprising ways (Curtis & Gough, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the difficulty to estimate correctly size distribution from NFIs data (due to the concentric sample plots design and the different plot radius between countries) made us give up the inclusion of size structure in the analysis. However recent studies found that stand productivity in mixed stands is related not only to species composition but to size structure (e.g., [73][74][75]). On the other hand, the main advantage of using data from NFIs is that they provide systematic information and therefore there are data of many species mixtures covering larger gradients of site and stand conditions than those available through other sample plots [21,30].…”
Section: Strengths and Limitations Of Nfi Databasesmentioning
confidence: 99%
“…We confirmed results obtained with two-species mixtures by Lu et al (2016) that found an overyielding in mixture of broadleaved and coniferous species which were also distant in their ST. This suggests that functional type and ST are complementary drivers, among other determinants, of the mixture effect on tree species productivity (Forrester, Kohnle, Albrecht, & Bauhus, 2013;Silva Pedro, Rammer, & Seidl, 2017;Yuan et al, 2016).…”
Section: Variablementioning
confidence: 99%